Recreation on Toronto Island, the Peoples’ Resort, 1793-1910 - Bain, David (Ontario History, 2019)
Toronto Island, known as ‘the Island,’ has always been the city of Toronto’s most distinctive and beloved popular resort. From the earliest days of British rule in the late eighteenth century, the island was a mix of the planned and unplanned, and, despite various government interventions, remained a unique blend throughout the nineteenth century and beyond. One goal of this article is to trace the recreational history of the Island in the nineteenth century. A second goal will be to trace the growth of its parkland and its role in shaping and altering the resort. The conclusion suggests reasons for the island’s continuing success and then sets forth a few thoughts for dealing with special landscapes in an urban setting.